Conservative Ideology in Community-Based Arts Education: An Ethnographic Study of Dance Learning - Treny Hera; Agus Cahyono; Malarsih Malarsih; Eko Sugiarto; Muhammad Fazli Taib Bin Saearani (AL-ISHLAH: Jurnal Pendidikan, 2025)
Community-based arts education plays a vital role in cultural preservation, yet it is often shaped by ideological forces. This ethnographic study explores how conservative ideology manifests within the traditional dance education practices of Sanggar Dinda Bestari in South Sumatra, Indonesia, and its implications for pedagogy, cultural identity, and intergenerational transmission. Using a qualitative ethnographic approach, data were collected over three months through participant observation, in-depth interviews with dance instructors, students, and studio managers, and documentation of teaching practices. Thematic analysis was conducted following Braun and Clarke’s framework, with critical discourse analysis used to examine power dynamics and ideological reproduction in dance pedagogy. Findings reveal that conservative ideology is embedded in dance learning through hierarchical teacher-student relationships, sacred framing of traditional repertoires, norms of modesty, and obedience in instruction. While these practices preserve cultural authenticity, they also restrict creative expression and dialogue, particularly among younger learners. Tensions arise between tradition and modernity, as seen in efforts to adapt dance instruction for social media or engage youth participation. Sanggar Dinda Bestari serves as both a site of cultural reproduction and ideological negotiation. While conservative values support continuity and discipline, they may also limit innovation. A hybrid pedagogical model that balances tradition with participatory and adaptive strategies is proposed. This study contributes to broader discourses on how ideology shapes non-formal arts education and offers insights into navigating cultural preservation in the context of globalization and generational change.